2023
DOI: 10.3847/1538-4357/acdfd2
|View full text |Cite
|
Sign up to set email alerts
|

Are Nonthermal Velocities in Active Region Coronal Loops Anisotropic?

Abstract: We have measured line widths in active region coronal loops in order to determine whether the nonthermal broadening is anisotropic with respect to the magnetic field direction. These nonthermal velocities are caused by unresolved fluid motions. Our analysis method combines spectroscopic data and a magnetic field extrapolation. We analyzed spectra from the Extreme Ultraviolet Imaging Spectrometer on Hinode. A differential emission measure analysis showed that many spectral lines that are commonly considered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…A few studies of the anisotropy of the nonthermal velocity confirm the existence of ξ ∥ but found different relationships between the two components ξ ∥ and ξ ⊥ , including ξ ∥ > ξ ⊥ (Hahn et al 2023) and ξ ∥ < ξ ⊥ (Hara & Ichimoto 1999). The possible candidates to create ξ ∥ and the relatively constant nonthermal widths in closed fields include reconnection (e.g., jets and nanoflares) or slow mode waves (Hahn et al 2023), but it is still difficult to reach a firm conclusion (Brooks & Warren 2016).…”
Section: Other Nonthermal Motionsmentioning
confidence: 99%
“…A few studies of the anisotropy of the nonthermal velocity confirm the existence of ξ ∥ but found different relationships between the two components ξ ∥ and ξ ⊥ , including ξ ∥ > ξ ⊥ (Hahn et al 2023) and ξ ∥ < ξ ⊥ (Hara & Ichimoto 1999). The possible candidates to create ξ ∥ and the relatively constant nonthermal widths in closed fields include reconnection (e.g., jets and nanoflares) or slow mode waves (Hahn et al 2023), but it is still difficult to reach a firm conclusion (Brooks & Warren 2016).…”
Section: Other Nonthermal Motionsmentioning
confidence: 99%
“…The emission of the spectral lines we use, from Fe XIV, XV, and XVI, represents an integration along the LOS and therefore potentially contains contributions from both the active region loop arcade and unresolved foreground and background emission. Hahn et al (2023) have quantified the unresolved component contribution to these lines in an active region, indicating substantial contributions, with an increasing impact as the line formation temperature decreases. This contribution may also be activeregion-dependent (Brown et al 2008).…”
Section: Introductionmentioning
confidence: 99%